BLESSING IN DISGUISE TEORI RECEPTIE: DAMPAK TEORI RECEPTIE PADA TRADISI PENYALINAN DAN PENULISAN ULANG MANUSKRIP HUKUM ADAT DAN UNDANG-UNDANG KERAJAAN ISLAM NUSANTARA - Anis Masykhur (Universitas Islam Negeri Mataram, 2020)
The political policy of the Dutch colonialists in the late 19th and early 20th centuries had followed up on Snouck Hurgronje’s recommendations, especially the relationship between Islam and politics and between Islam and adat. One of the recommendations was that Islam must be separated from the political aspect. In terms of relations with customary law, Islamic law can only be enforced when it be recognized by customary law, which is then known as the receptie theory. The implementation of this theory had been clearly of negative value for the existence of Islamic law. However, the positive side cannot be ignored. Some of the policies carried out by the colonizers were mobilizing the kingdoms in the archipelago to record the acts of kingdoms or applicable customary law by transmitting manuscripts from previous works. This research is a study of customary law documents and statute manuscripts those have been enforced in several Islamic kingdoms by looking at the writing, promulgation and re-copying period. The analysis is equipped with a historical approach. The findings of this study that after the acceptance of the receptie theory, rewriting of customary law documents was most intensive and its peak when it was recorded in 45 volumes adatrechtbundels. Volume I was first printed in 1910 AD. By that, the Government emphasized that the law that had been applied was a customary law. Whereas by featuring the customary law, in essence it also accentuated the Islamic law.